2020
DOI: 10.1111/1462-2920.14953
|View full text |Cite
|
Sign up to set email alerts
|

Expression and regulation of the mer operon in Thermus thermophilus

Abstract: Summary Mercury (Hg) is a highly toxic and widely distributed heavy metal, which some Bacteria and Archaea detoxify by the reduction of ionic Hg (Hg[II]) to the elemental volatile form, Hg(0). This activity is specified by the mer operon. The mer operon of the deeply branching thermophile Thermus thermophilus HB27 encodes for, an O‐acetyl‐l‐homoacetylserine sulfhydrylase (Oah2), a transcriptional regulator (MerR), a hypothetical protein (hp) and a mercuric reductase (MerA). Here, we show that this operon has t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…The mer and chr operons confer resistance to mercury and chromium, respectively. The mer operon is widely distributed in bacteria and has a complex composition [32,33]. MerC, MerP, and MerT are the key components for the recognition and uptake of Hg 2+ .…”
Section: Introductionmentioning
confidence: 99%
“…The mer and chr operons confer resistance to mercury and chromium, respectively. The mer operon is widely distributed in bacteria and has a complex composition [32,33]. MerC, MerP, and MerT are the key components for the recognition and uptake of Hg 2+ .…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the sulfate reducing bacteria in the natural environment can make MeHg demethylation [12] , it is also found that selenium compounds can regulate the abundance of sulfate reducing bacteria in the intestinal tract of MeHg poisoned rats, thereby promoting the demethylation of MeHg in vivo [13][14] . Genetically, it was found that the hgcAB gene cluster and the mer operon is responsible for demethylation of MeHg [15] . Anaerobic microorganisms possessing these genes, such as sulfate-reducing bacteria and pseudomonas have been found to degrade MeHg [16][17] .…”
Section: Introductionmentioning
confidence: 99%